2016
DOI: 10.1542/peds.2015-0463
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Versus Term Children: Analysis of Sedation/Anesthesia Adverse Events and Longitudinal Risk

Abstract: BACKGROUND AND OBJECTIVES: Preterm and former preterm children frequently require sedation/ anesthesia for diagnostic and therapeutic procedures. Our objective was to determine the age at which children who are born <37 weeks gestational age are no longer at increased risk for sedation/anesthesia adverse events. Our secondary objective was to describe the nature and incidence of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 39 publications
4
30
0
1
Order By: Relevance
“…Former preterm infants have an increased risk of postanesthesia apnea, 377 but it is unclear whether a similar risk is associated with sedation, because this possibility has not been systematically investigated. 378 Other concerns regarding the effects of anesthetic drugs and sedating medications on the developing brain are beyond the scope of this document. At this point, the research in this area is preliminary and inconclusive at best, but it would seem prudent to avoid unnecessary exposure to sedation if the procedure is unlikely to change medical/dental management (eg, a sedated MRI purely for screening purposes in preterm infants).…”
Section: Neonates and Former Preterm Infantsmentioning
confidence: 99%
“…Former preterm infants have an increased risk of postanesthesia apnea, 377 but it is unclear whether a similar risk is associated with sedation, because this possibility has not been systematically investigated. 378 Other concerns regarding the effects of anesthetic drugs and sedating medications on the developing brain are beyond the scope of this document. At this point, the research in this area is preliminary and inconclusive at best, but it would seem prudent to avoid unnecessary exposure to sedation if the procedure is unlikely to change medical/dental management (eg, a sedated MRI purely for screening purposes in preterm infants).…”
Section: Neonates and Former Preterm Infantsmentioning
confidence: 99%
“…However concern has been raised about possible long-term adverse effects resulting from sedation and anesthesia [14]. For example, a recent report stated that 8.6% of all children under sedation/anesthesia experienced an adverse event, most of which were minor, and 57.7% of those events occurred during MRI scans, more often than any other ordered procedure [5]. In view of studies such as this, there is an increasing need to develop techniques for motion-robust MRI in young patients to help avoid using sedation in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…This higher incidence of AE in patients with cerebral palsy could be attributed to multiple factors such as muscle tone, pharyngeal collapse, increased secretions and drug interactions with various medications used daily such as baclofen 20 . We excluded all patients with a recent active upper respiratory infection as sedation candidates as there are some publications which have elucidated to the higher risk of adverse events and sedation failure in these patients 21] The risk for AE in our patients with prematurity, gastrooesophageal reflux disease and cardiac disease was not statistically significant, although studies have shown that these patients are at higher risk for AE with sedation 15,22,23,24 . This study has several limitations.…”
Section: Discussionmentioning
confidence: 98%